Penyuluhan Peluang Ekspor Komoditas Teh Produk UMKM Kemuning Ngargoyoso Karanganyar Ke Uzbekistan - Rahmawati Setiyani; Bobur Sobirov (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Karanganyar Regency is one of the districts that has potential in the agricultural sector. One of agricultural commodities in Karanganyar Regency is tea. The tea plantation products in Karanganyar Regency are processed by MSMEs in the Kemuning, Ngargoyoso, Karanganyar area. Tea produced by MSMEs Kemuning, Ngargoyoso, Karanganyar is marketed in the domestic market. Partners in the Community Service activity are MSMEs in Kemuning, Ngargoyoso, Karanganyar. The problem faced by partners have regarding export opportunities for tea they produce. The aim of implementing Community Service is to provide education regarding export opportunities for tea produced by MSMEs Kemuning, Ngargoyoso, Karanganyar to Uzbekistan and increase the quality value and competitiveness of tea produced through proper post harvest management. The methods used in Community Service are counseling, demonstration and evaluation. The results of the Community Service activities are that participants are enthusiastic about taking part in Community Service activities, and the activities can increase participant’s understanding and insight regarding tea export opportunities to Uzbekistan, as well as understanding the importance of post harvest management of tea to increase the quality value and competitiveness of tea products.